ОСОБЛИВОСТІ ФОРМУВАННЯ ГОТОВНОСТІ ДО ТВОРЧОЇ ДІЯЛЬНОСТІ В ПЕДАГОГІЧНОМУ ПРОЦЕСІ ВИЩОЇ ШКОЛИ (Педагогіка вищої та середньої школи, 2002)
This article deals with the question of the formation of student creative abilities. The author shows the specific conditions to form students' creative abilities at schools of higher learning.